How Bad Is Antidumping? Evidence from Panel Data - Egger, Peter; Nelson, Douglas (The Review of Economics and Statistics, 2011)
Current research on antidumping suggests a number of channels through which antidumping affects the volume of world trade. This paper uses a structural approach to the gravity model framework to evaluate these hypotheses using data on trade volume over the period 1948 to 2001. We conclude that the volume and welfare effects have been negative but quite modest.